Modal Simbolik Kreator Konten Kecantikan di Kota Denpasar - Tambunan, Delsie Evangeline; Nugroho, Wahyu Budi; Aditya, I Gst. Ngr. Agung Krisna (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This study aims to analyze the process of converting symbolic capital owned by beauty content creators in Denpasar City into economic capital, as well as to identify the role of other forms of capital such as social, economic, and cultural capital in supporting this process. This study is motivated by the widespread use of social media as a marketing tool and the emergence of the content creator profession as a key actor in the digital beauty industry. The approach used in this study is descriptive qualitative with data collection methods through observation, interviews, and documentation. The results show that symbolic capital such as accent, grammar, pronunciation, and language style plays a central role in building the image and trust of the audience. In addition, symbolic capital used by content creators in the form of visual aesthetics and self-image planning supports content creation. This symbolic capital is then converted into economic capital through collaboration with beauty brands and monetization of content on social media. Furthermore, the presence of social capital, economic capital, and cultural capital also strengthens the position of creators in the industry. Thus, it can be concluded that the success of beauty content creators in the digital world is not solely determined by popularity, but by their ability to strategically manage and actualize the various forms of capital they possess. This study is expected to contribute to the development of studies in beauty sociology, consumption sociology, postmodern sociology, gender sociology, economic sociology, and studies of the social body. Keywords: symbolic capital, content creator, beauty, social media